2015
DOI: 10.1186/s13059-014-0569-x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of DNA methylation in human adipose tissue reveals differential modification of obesity genes before and after gastric bypass and weight loss

Abstract: BackgroundEnvironmental factors can influence obesity by epigenetic mechanisms. Adipose tissue plays a key role in obesity-related metabolic dysfunction, and gastric bypass provides a model to investigate obesity and weight loss in humans.ResultsHere, we investigate DNA methylation in adipose tissue from obese women before and after gastric bypass and significant weight loss. In total, 485,577 CpG sites were profiled in matched, before and after weight loss, subcutaneous and omental adipose tissue. A paired an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
197
7
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(212 citation statements)
references
References 118 publications
(147 reference statements)
6
197
7
2
Order By: Relevance
“…However, after correction for multiple testing, Arner and colleagues were unable to find significant associations between the investigated methylation sites and insulin resistance in this cohort. Nevertheless, they present thousands of differentially methylated sites based on a nominal association, and validate their results by showing that some of them are also found in similar studies of DNA methylation in adipose tissue related to BMI, type 2 diabetes or weight loss [6,[9][10][11]. For example, 591 differentially methylated sites identified in adipose tissue of individuals with type 2 diabetes compared with nondiabetic controls in a study by Nilsson et al were also found to be nominally associated with insulin resistance in the study by Arner et al [6,9].…”
Section: Dnmt Dna (Cytosine-5)-methyltransferase Pbmc Peripheral Bloomentioning
confidence: 94%
See 1 more Smart Citation
“…However, after correction for multiple testing, Arner and colleagues were unable to find significant associations between the investigated methylation sites and insulin resistance in this cohort. Nevertheless, they present thousands of differentially methylated sites based on a nominal association, and validate their results by showing that some of them are also found in similar studies of DNA methylation in adipose tissue related to BMI, type 2 diabetes or weight loss [6,[9][10][11]. For example, 591 differentially methylated sites identified in adipose tissue of individuals with type 2 diabetes compared with nondiabetic controls in a study by Nilsson et al were also found to be nominally associated with insulin resistance in the study by Arner et al [6,9].…”
Section: Dnmt Dna (Cytosine-5)-methyltransferase Pbmc Peripheral Bloomentioning
confidence: 94%
“…Since the insulin-resistant women in the Arner et al study also have a higher BMI, it is difficult to conclude whether these 1973 sites are primarily associated with higher BMI rather than insulin sensitivity. It should also be noted that Arner et al found 91 differentially methylated sites that overlapped with sites that changed methylation in adipose tissue after weight loss induced by bariatric surgery [6,11]. Whether differential methylation of these sites contributes to improved insulin sensitivity needs to be further tested.…”
Section: Dnmt Dna (Cytosine-5)-methyltransferase Pbmc Peripheral Bloomentioning
confidence: 99%
“…35 The corresponding genes POLK for cg05673882 and ALPP for cg23667432 are oncogenes that play roles in the formation of several age-related cancers, including breast, prostate, lung, and ovarian cancers. [36][37][38][39] The biologic functions of the remaining 3 loci within unassigned genome regions are not yet known, only locus cg01127300 has been disclosed as a potential epigenetic regulator of obesity, 40 one of the deficits of the frailty syndrome. 41 Interestingly, neither of the most strongly smoking-related CpG sites, cg05575921 (AHRR) or cg03636183 (F2RL3), 26 was identified to be related to the FI in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…10 In addition, EWAS have been conducted to investigate associations of body mass index (BMI) or birth weight with DNA methylation in one tissue such as blood, and the candidate CpG sites were further examined in another tissue such as adipose tissue. [11][12][13][14][15][16] Several epigenetic biomarkers associated with BMI were identified, such as DNA methylation of HIF3A. 13 Some studies showed that corresponding methylation markers in peripheral blood have consistent associations as those discovered in adipose tissue.…”
Section: Introductionmentioning
confidence: 99%